2020
DOI: 10.3389/fcimb.2020.601072
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsins in Bacteria-Macrophage Interaction: Defenders or Victims of Circumstance?

Abstract: Macrophages are the first encounters of invading bacteria and are responsible for engulfing and digesting pathogens through phagocytosis leading to initiation of the innate inflammatory response. Intracellular digestion occurs through a close relationship between phagocytic/endocytic and lysosomal pathways, in which proteolytic enzymes, such as cathepsins, are involved. The presence of cathepsins in the endo-lysosomal compartment permits direct interaction with and killing of bacteria, and may contribute to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 230 publications
(313 reference statements)
0
38
0
Order By: Relevance
“…Indeed, at high concentrations, NSPs have demonstrated potent antimicrobial activity against many respiratory pathogens including Streptococcus pneumoniae , Klebsiella pneumoniae and P. aeruginosa [ 117 , 118 , 119 ]. In macrophages, the mantle for intracellular pathogen killing by non-oxidative means is also taken up by the lysosomal cathepsins [ 120 , 121 ]. Furthermore, the processing and trafficking of certain Toll-like receptors (TLRs), vital receptors for the recognition of microbial membrane products and nucleic acids, appears to be dependent on intracellular cathepsins and asparagine endopeptidase, also known as legumain [ 122 , 123 ].…”
Section: Proteases and Mucosal Immunitymentioning
confidence: 99%
“…Indeed, at high concentrations, NSPs have demonstrated potent antimicrobial activity against many respiratory pathogens including Streptococcus pneumoniae , Klebsiella pneumoniae and P. aeruginosa [ 117 , 118 , 119 ]. In macrophages, the mantle for intracellular pathogen killing by non-oxidative means is also taken up by the lysosomal cathepsins [ 120 , 121 ]. Furthermore, the processing and trafficking of certain Toll-like receptors (TLRs), vital receptors for the recognition of microbial membrane products and nucleic acids, appears to be dependent on intracellular cathepsins and asparagine endopeptidase, also known as legumain [ 122 , 123 ].…”
Section: Proteases and Mucosal Immunitymentioning
confidence: 99%
“…Proteolytic enzymes like cathepsins participate in the intracellular digestion of bacteria. This event contributes directly to the elimination of the invading pathogen and indirectly to the generation of bacterial antigens for presentation, thus supporting adaptive immune responses ( 44 ). We found that Rickettsia -infected THP-1 macrophages displayed reductions in the amounts of cathepsin A/lysosomal protective protein (CtsA), cathepsin D (CtsD), and cathepsin Z (CtsZ) at 24 hpi.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with our previous observations of lower accumulation of CtsD and CtsZ in macrophages infected with the highly pathogenic R. conorii ( 23 ). Many bacterial pathogens have evolved multiple strategies for controlling the expression and proteolytic activity of cathepsins to limit their antibacterial action and subsequently favor intracellular pathogen survival ( 44 48 ). Therefore, understanding the cathepsin modulation strategies of Rickettsia and how the dysregulation of these proteases contributes to the pathogenesis of rickettsial infections through their role in both innate and adaptive immune functions of macrophages warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that Ah infection tends to affect the process of phagolysosomal killing by downregulating several proteins involved in the process. Proteins like Cathepsins, Tpp1, Ppt1 are cysteine and serine proteases or hydrolases that may play role in pathogen killing (31,32). Vatpase enzymes are important for maintaining the acidic pH inside the lysosomes whereas the other proteins (as Rab proteins) are important for cargo transportation inside the cell (33).…”
Section: Discussionmentioning
confidence: 99%